SMU launches new degree programmes in Computer Science and Computing & Law - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
With the rapid growth of the digital economy and the ongoing efforts to transform Singapore through technology, there is strong demand in the public and private sectors for graduates with sound knowledge and training in computing. Based on IMDA’s Annual Survey for Infocomm Media Manpower that was conducted in 2017, there is a strong demand for skilled professionals, as enterprises have forecast infocomm professionals to grow by 28,500 between 2018 and 2020. In response to these industry trends and demand, the School of Information Systems at Singapore Management University (SMU) has strengthened its undergraduate curriculum with the introduction of two new degree programmes - Bachelor of Science (Computer Science) from the new academic year commencing in August 2019, and Bachelor of Science (Computing & Law) in August 2020.